Synthesis and optoelectronic properties of benzoquinone-based donor–acceptor compounds - Sutherland, Daniel R.; Sharma, Nidhi; Rosair, Georgina M.; Samuel, Ifor D. W.; Lee, Ai-Lan; Zysman-Colman, Eli (Beilstein Journal of Organic Chemistry, 2019)
Herein, we report a mild and efficient palladium-catalyzed C–H functionalization method to synthesize a series of benzoquinone (BQ)-based charge-transfer (CT) derivatives in good yields. The optoelectronic properties of these compounds were explored both theoretically and experimentally and correlations to their structures were identified as a function of the nature and position of the donor group (meta and para) attached to the benzoquinone acceptor. Compound 3, where benzoquinone is para-conjugated to the diphenylamine donor group, exhibited thermally activated delayed fluorescence (TADF) with a biexponential lifetime characterized by a prompt ns component and a delayed component of 353 μs.
Keywords: materials chemistry; physical organic chemistry; spectroscopy; thermally activated delayed fluorescence

(untitled) - Abraham, I.; Joshi, R.; Pardasani, P.; Pardasani, R. T. (J. Braz. Chem. Soc., 2011)

(untitled) - Wang, Y.; Zhu, S.; Zou, L.-H. (Eur. J. Org. Chem., 2019)

(untitled) - Dandawate, P. R.; Vyas, A. C.; Padhye, S. B.; Singh, M. W.; Baruah, J. B. (Mini-Rev. Med. Chem., 2010)

Naturally Occurring Quinones IV - Recent Advances - Thomson, R. H. (Springer, 1997)

Handbook of Natural Colorants - Bechtold, T. (Natural Colorants – Quinoid, Naphthoquinoid and Anthraquinoid Dyes, 2009)

(untitled) - Itami, K.; Palmgren, A.; Thorarensen, A.; Bäckvall, J.-E. (J. Org. Chem., 1998)

(untitled) - Lyons, T. W.; Hull, K. L.; Sanford, M. S. (J. Am. Chem. Soc., 2011)

(untitled) - Palmgren, A.; Thorarensen, A.; Bäckvall, J.-E. (J. Org. Chem., 1998)

(untitled) - Ura, Y.; Sato, Y.; Shiotsuki, M.; Suzuki, T.; Wada, K.; Kondo, T.; Mitsudo, T.-a. (Organometallics, 2003)

(untitled) - Decharin, N.; Stahl, S. S. (J. Am. Chem. Soc., 2011)

(untitled) - Kwon, J. E.; Hyun, C.-S.; Ryu, Y. J.; Lee, J.; Min, D. J.; Park, M. J.; An, B.-K.; Park, S. Y. (J. Mater. Chem. A, 2018)

(untitled) - Klare, J. E.; Tulevski, G. S.; Sugo, K.; de Picciotto, A.; White, K. A.; Nuckolls, C. (J. Am. Chem. Soc., 2003)

(untitled) - Petrangolini, P.; Alessandrini, A.; Facci, P. (J. Phys. Chem. C, 2013)

(untitled) - Walker, S. E.; Jordan-Hore, J. A.; Johnson, D. G.; Macgregor, S. A.; Lee, A.-L. (Angew. Chem., Int. Ed., 2014)

(untitled) - Jardim, G. A. M.; Bower, J. F.; da Silva Júnior, E. N. (Org. Lett., 2016)

(untitled) - Honraedt, A.; Le Callonnec, F.; Le Grognec, E.; Fernandez, V.; Felpin, F.-X. (J. Org. Chem., 2013)

(untitled) - Fujiwara, Y.; Domingo, V.; Seiple, I. B.; Gianatassio, R.; Del Bel, M.; Baran, P. S. (J. Am. Chem. Soc., 2011)

(untitled) - Ilangovan, A.; Polu, A.; Satish, G. (Org. Chem. Front., 2015)

(untitled) - Singh, P. P.; Aithagani, S. K.; Yadav, M.; Singh, V. P.; Vishwakarma, R. A. (J. Org. Chem., 2013)

(untitled) - Wang, J.; Wang, S.; Wang, G.; Zhang, J.; Yu, X.-Q. (Chem. Commun., 2012)

(untitled) - Shaaban, S.; Jolit, A.; Petkova, D.; Maulide, N. (Chem. Commun., 2015)

Highly Efficient OLEDs with Phosphorescent Materials - Yersin, H. (Wiley-VCH, 2007)

(untitled) - Partee, J.; Frankevich, E. L.; Uhlhorn, B.; Shinar, J.; Ding, Y.; Barton, T. J. (Phys. Rev. Lett., 1999)

(untitled) - Wong, M. Y.; Zysman-Colman, E. (Adv. Mater. (Weinheim, Ger.), 2017)

(untitled) - Endo, A.; Ogasawara, M.; Takahashi, A.; Yokoyama, D.; Kato, Y.; Adachi, C. (Adv. Mater. (Weinheim, Ger.), 2009)

(untitled) - Uoyama, H.; Goushi, K.; Shizu, K.; Nomura, H.; Adachi, C. (Nature, 2012)

(untitled) - Im, Y.; Kim, M.; Cho, Y. J.; Seo, J.-A.; Yook, K. S.; Lee, J. Y. (Chem. Mater., 2017)

(untitled) - Bixon, M.; Jortner, J.; Cortes, J.; Heitele, H.; Michel-Beyerle, M. E. (J. Phys. Chem., 1994)

(untitled) - Zhang, Q.; Kuwabara, H.; Potscavage, W. J., Jr; Huang, S.; Hatae, Y.; Shibata, T.; Adachi, C. (J. Am. Chem. Soc., 2014)

(untitled) - Perdew, J. P.; Ernzerhof, M.; Burke, K. (J. Chem. Phys., 1996)

(untitled) - Grimme, S. (Chem. Phys. Lett., 1996)

(untitled) - Ji, X.; Banks, C. E.; Silvester, D. S.; Wain, A. J.; Compton, R. G. (J. Phys. Chem. C, 2007)

(untitled) - Lu, R.; Chen, W.; Li, W.-W.; Sheng, G.-P.; Wang, L.-J.; Yu, H.-Q. (Front. Environ. Sci. Eng., 2017)

(untitled) - Tomkeviciene, A.; Grazulevicius, J. V.; Volyniuk, D.; Jankauskas, V.; Sini, G. (Phys. Chem. Chem. Phys., 2014)

(untitled) - Connelly, N. G.; Geiger, W. E. (Chem. Rev., 1996)

(untitled) - Cardona, C. M.; Li, W.; Kaifer, A. E.; Stockdale, D.; Bazan, G. C. (Adv. Mater. (Weinheim, Ger.), 2011)

(untitled) - Albarran, G.; Boggess, W.; Rassolov, V.; Schuler, R. H. (J. Phys. Chem. A, 2010)

(untitled) - Ishida, H.; Tobita, S.; Hasegawa, Y.; Katoh, R.; Nozaki, K. (Coord. Chem. Rev., 2010)

(untitled) - Molard, Y.; Dorson, F.; Brylev, K. A.; Shestopalov, M. A.; Le Gal, Y.; Cordier, S.; Mironov, Y. V.; Kitamura, N.; Perrin, C. (Chem. – Eur. J., 2010)

(untitled) - Aloïse, S.; Ruckebusch, C.; Blanchet, L.; Réhault, J.; Buntinx, G.; Huvenne, J.-P. (J. Phys. Chem. A, 2008)

(untitled) - Barbafina, A.; Elisei, F.; Latterini, L.; Milano, F.; Agostiano, A.; Trotta, M. (Photochem. Photobiol. Sci., 2008)

(untitled) - Itoh, T. (Chem. Rev., 1995)